A Synergy Between Endotoxin and (1→3)-Beta-D-Glucan Enhanced Neutrophil Extracellular Traps in Candida Administered Dextran Sulfate Solution Induced Colitis in FcGRIIB-/- Lupus Mice, an Impact of Intestinal Fungi in Lupus - Saithong S; Saisorn W; Visitchanakun P; Sae-khow K; Chiewchengchol D; Leelahavanichkul A (Dove Medical Press, 2021)
Supichcha Saithong,1– 3 Wilasinee Saisorn,3 Peerapat Visitchanakun,3 Kritsanawan Sae-khow,3 Direkrit Chiewchengchol,2,3 Asada Leelahavanichkul2,3 1Medical Microbiology, Interdisciplinary and International Program, Graduate School, Chulalongkorn University, Bangkok, Thailand; 2Immunology Unit, Department of Microbiology, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 3Translational Research in Inflammation and Immunology Research Unit (TRIRU), Department of Microbiology, Chulalongkorn University, Bangkok, ThailandCorrespondence: Asada Leelahavanichkul; Direkrit ChiewchengcholImmunology Unit, Department of Microbiology, Chulalongkorn University, Bangkok, 10330, ThailandTel +66-2-256-4251Fax +66-2-252-6920Email aleelahavanit@gmail.com; cdirekrit@live.comIntroduction: The translocation of organismal molecules from gut into blood circulation might worsen the disease severity of lupus through the induction of neutrophil extracellular traps (NETs).Methods: An impact of lipopolysaccharide (LPS) and (1→ 3)-β-D-glucan (BG), components of gut bacteria and fungi, respectively, on NETs formation, was explored in lupus models, Fc gamma receptor IIB deficiency (FcGRIIB-/-) and Pristane injection, using Candida-administered dextran sulfate solution induced colitis (Candida-DSS) model.Results: Severity of Candida-DSS in FcGRIIB-/- mice was more prominent than wild-type (WT) and Pristane mice as indicated by (i) colonic NETs using immunofluorescence of Ly6G, myeloperoxidase (MPO) and neutrophil elastase (NE) together with expression of PAD4 and IL-1β, (ii) colonic immunoglobulin (Ig) deposition (immunofluorescence), (iii) gut-leakage by FITC-dextran assay, endotoxemia and serum BG, (iv) systemic inflammation (neutrophilia, serum cytokines, serum dsDNA and anti-dsDNA) and (v) renal injury (proteinuria, glomerular NETs and Ig deposition).Discussion: The formation of NETs in Candida-DSS mice was more severe than non-Candida-DSS mice and NETs in Candida-DSS were more profound in FcGRIIB-/- mice than Pristane mice. Prominent NETs in Candida-DSS FcGRIIB-/- mice might be due to the profound responses against LPS+BG in FcGRIIB-/- neutrophils compared with WT cells. These data implied an impact of the inhibitory FcGRIIB in NETs formation and an influence of gut fungi in lupus exacerbation. Hence, gut fungi in a DSS-induced gut-leakage lupus model enhanced colonic NETs that facilitated gut translocation of organismal molecules and synergistically exacerbated lupus activity.Keywords: FcGRIIB deficient mice, Pristane mice, systemic lupus erythematosus, neutrophil extracellular traps, Candida, gut-leakage